Study on Social Media Users and Its Relation to the e-Commerce Activities on Youth in Indonesia - Irawan, Krisma Budianto; Ipung, Heru Purnomo; Galinium, Maulahikmah (Swiss German University, 2016)
Internet, Social Media and e-Commerce are three most common thingspeople could find and usually interact with nowadays. Internet has beenpart of our basic daily needs: no one can work professionally withoutbeing connected to the network even once in a day. Those people usuallyalso have at least one Social Media accounts; as well know about theexistence of e-Commerce markets. Also, Social Media and e-CommerceChannel nowadays more likely to interact with each other: peoplespreading the word about their commerce in the Social Networks. Basedon that fact, this research purpose is to find out which factors, based onthe Technology Acceptance Model, is playing the huge role on this socalled relations between the interaction of people in the Social Media andtheir activities in the e-Commerce, especially on Indonesian youth. Itturns out, that Voluntariness has 55% contribution towards this relations,as well as Job Relevance, Result Demonstrability and Computer SelfEfficacy with 63%, 60% and 58% contributions respectively.